Therapeutic management of a symptomatic Kaposi's sarcoma patient with renal failure undergoing haemodialysis: A case report - Anna Passarelli; Giovanna Galdo; Teresa Pellegrino; Giandomenico Roviello; Michele Aieta; Raffaele Conca (PAGEPress Publications, 2021)
Kaposi's sarcoma (KS) is a rare inflammation-based vascular cancer involving the skin. The viral aetiology of KS is the human herpesvirus 8 (HHV-8). KS may be frequently diagnosed in immunosuppressed kidney-transplanted patients, while is less common in patients with dialysis. It is known that various immunological abnormalities can lead to impaired immune status in uremic patients. It is noteworthy that despite the incidence of KS in patients with renal impairment, only few cases have reported efficacy and safety profile of KS targeting anti-cancer drugs in this kidney disease population. Herein, we report the first case of a symptomatic KS patient with renal disease in haemodialysis and focus on its therapeutic management. We also review the main data available from literature regarding the safety of KS therapy in dialysis patients.